Analisis Efisiensi Proses dan Pengendalian Waste Material Menggunakan Pendekatan Lean Manufacturing pada PT XYZ - Harun Arrasid; Muhamad Afiffurohman; Marjuni Marjuni (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Increasing industrial competition and rising raw material costs are compelling companies to improve production process efficiency by reducing material waste. This study aims to analyze the impact of using an automatic crusher on production process efficiency compared to manual methods, as well as to examine its application within the Lean Manufacturing framework. The research results indicate that crusher automation increases processing capacity from 60–80 kg/hour to 800–1,800 kg/hour and boosts recycled material output from 900–1,500 kg/day to 1,800–2,800 kg/day. The implementation of this technology successfully reduced unmanaged material waste to 5–10 kg/day, trimmed labor requirements from 5 to 4 operators, and eliminated non-value-added activities (waiting and overprocessing). Although there is a trade-off in the form of increased operational electricity costs, the overall improvement in productivity has a significant positive impact on production system efficiency and supports the pillars of Lean Manufacturing through the elimination of waste.